Silencing of developmental genes in Hydra - Lohmann, Jan U.; Endl, Ingrid; Bosch, Thomas C. G. (Developmental biology, 1999)
Numerous developmental control genes have been isolated in a variety of organisms by either homology cloning or system-specific strategies. Functional genetic tests, however, are available for only a few model organisms and particularly are missing in a number of animals that occupy key positions for understanding the evolution of development and gene function. Double-stranded RNA-mediated interference (RNAi) opens a way to perform functional studies in such “nongenetic” organisms. Here we show that RNAi can be used to test the function of developmental genes in the cnidarian Hydra, a classical model for developmental studies. Introduction of double-stranded RNA corresponding to the head-specific gene ks1 caused strong depletion of ks1 transcripts. ks1 loss-of-function polyps exhibited severe defects in head formation, indicating an important role of ks1 in Hydra head development. Our results demonstrate for the first time efficient gene silencing in Hydra. RNAi provides an entry point for a variety of functional studies and a direct approach for analyzing the hierarchy of regulatory genes in Hydra, which until now has not been amenable to loss-of-function genetics.